ANTIBACTERIAL EFFECTIVENESS OF BLACK QUICK (Nigella sativa Linn) EXTRACT ON BACTERIA INHIBITORY Aeromonas hydrophila, AND MORPHOLOGY FISH INDIGO (Oreochromis niloticus) POST INFECTION - Dwi Elfa Maharani; Salnida Yuniarti Lumbessy; Fariq Azhar (Journal of Fish Health, 2022)
The main problem in cultivation is a disease that causes less optimal growth and even death. This study aims to analyze the effectiveness of black cumin extract on the inhibition of A. hydrophila bacteria, analyze its active ingredients, analyze its toxicity level to Tilapia, and analyze the effect of the extract on the survival rate and morphology of Tilapia after being infected with A. hydrophila bacteria. The method used was a completely randomized design (CRD) which consisted of 3 stages. Inhibition zone with 5 treatments 2 repetitions, namely P0 (aquades), P1 (25%), P2 (50%), P3 (75%), and P4 (100%). LC50 with 4 treatments 2 replications using regression analysis with the help of the probit table. In Vivo with 6 treatments, 3 replicates, namely P0 (NaCl injection) as a control-, P1 (bacterial injection) as control+, P2 (250 ppm), P3 (500 ppm), P4 (750 ppm), P5 (1000 ppm). The results showed that black cumin seed extract with various concentrations affected the inhibition of A. hydrophila, SR, and Tilapia morphology after infection with bacteria. The test of inhibition with concentrations of 25%, 50%, 75%, and 100% can inhibit the growth of bacteria A. hydrophila because it contains antibacterial activity compounds. The extract has toxic properties to Tilapia (LC50=220.23 ppm). Soaking fish for 30 minutes in the I n Vivo test P3 treatment is the best treatment because it can provide a high SR of 73.3 %. However, at high concentrations, it can reduce fish survival.